2015
DOI: 10.1364/oe.23.025959
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced periodic surface structures on titanium upon single- and two-color femtosecond double-pulse irradiation

Abstract: Single- and two-color double-fs-pulse experiments were performed on titanium to study the dynamics of the formation of laser-induced periodic surface structures (LIPSS). A Mach-Zehnder inter-ferometer generated polarization controlled (parallel or cross-polarized) double-pulse sequences in two configurations - either at 800 nm only, or at 400 and 800 nm wavelengths. The inter-pulse delays of the individual 50-fs pulses ranged up to some tens of picoseconds. Multiple of these single- or two-color double-fs-puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…2a -5a) it was found that the orientation of LSFL on copper is always perpendicular to the polarization of the incident laser radiation, where the period is Λ (LSF L) ≈ 0.5 λ. Moreover, according to the literature [21,22], when higher fluences are applied, additionally to the LSFL in the center, HSFL are observed in the edge, where the light intensity is lower, with orientation parallel to the polarization. In the second set of our experiments, a contradicting behavior is illustrated, where the ripples at higher fluences 0.54−0.9 J/cm 2 appear to have two different orientations, perpendicular to each other, but they all belong to LSFL.…”
Section: Resultsmentioning
confidence: 77%
“…2a -5a) it was found that the orientation of LSFL on copper is always perpendicular to the polarization of the incident laser radiation, where the period is Λ (LSF L) ≈ 0.5 λ. Moreover, according to the literature [21,22], when higher fluences are applied, additionally to the LSFL in the center, HSFL are observed in the edge, where the light intensity is lower, with orientation parallel to the polarization. In the second set of our experiments, a contradicting behavior is illustrated, where the ripples at higher fluences 0.54−0.9 J/cm 2 appear to have two different orientations, perpendicular to each other, but they all belong to LSFL.…”
Section: Resultsmentioning
confidence: 77%
“…The laser would generate a shockwave and induce the recoil pressure inside the material. The recoil pressure would push the thin molten material above the surface and present protrusion structures [ 18 , 27 ]. For the formation of 2D nanostructures, it is speculated that in the second irradiation, due to the sub-surface cavitation [ 25 ], there will be an effect under the first structure, causing the first structure expanded above the initial position, and then forming 2D-HSFL net-like structures, as shown in Figure 5 e,f.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of selforganised microstructures by femtosecond laser structuring is a well-investigated and intensely discussed topic in laser structuring. [45][46][47][48] The laser induced periodic surface structures (LIPSS) are formed perpendicular to the polarization of the laser beam with a periodicity in the order of the laser beam or slightly below. With laser pulses on the picosecond timescale such parallel lines have been identied, too.…”
Section: Discussionmentioning
confidence: 99%